Calcium absorption and bone retention in a model of growing rats: Effect of feeding an experimental yogurt-reduced in lactose-containing galactooligosaccharides (GOS) - Seijo, Mariana (2021)
GOS are natural prebiotic of maternal milk. They can be enzymatically synthetized in yogurt manufacture from milk lactose obtaining a dairy product reduced in lactose containing prebiotics and potentially probiotics. It was evaluated if this yogurt containing GOS and reduced in lactose (EY) offered some extra advantages as compared to a regular yogurt (RY) in calcium (Ca) and phosphate (Pi) absorption (Abs) and bone retention during normal growth. Male weaning rats received control diet (C), EY or regular yogurt (RY) during 28 days. Results showed no differences in food consumption and body weight between C and yogurts groups. EY showed the highest increase in fecal lactobacillus colonies, in short chain fatty acids production especially propionate and butyrate, in large intestinal crypt deep, and the lowest caecum pH, CaAbs% increased significantly as follows: EY>RY>C (p<0.05); PiAbs% was higher in EY vs. RY. Femur Ca and Pi content, bone mineral content, density and biomechanical parameters were similar in EY and C but lower in RY (p<0.05). The epiphyseal and hypertrophic cartilage widths were lower in EY and RY than in C (p<0.05) while total cartilage width was similar in EY and C. Conclusion: EY reduced in lactose increased mineral Abs attaining C group bone retention and quality while RY diet consumption did not achieve bone growth and quality of C group. Then EY would be a good strategy to attain an adequate peak bone mass during growth, especially in lactose intolerant subjects. Grant of UBACyT and CONICET.